CHINA’S APPROACH TO MULTILATERALISM WITH AN EMPHASIS ON ITS INFLUENCE IN CENTRAL ASIA - SHAMSHIDOV, Kushtarbek (CENTRAL ASIA AND THE CAUCASUS, 2012)
This research considers that from a regional perspective, multilateralism can be an effective way to understand great power behavior on the international arena. The way emerging great powers interact with neighboring countries, and the way they work with regional powers has always been one of the best indicators of their future intentions as a great power. This concept proves very useful when examining an emerging power’s capacity and attempting to predict its future behavior in the international system. There is tremendous speculation around what kind of China we are going to see in the near future, particularly if China surpasses all other states eco nomically. The objective of this research is to contribute to this question by examining China’s use of multilateralism in its near neighborhood, more specifically by examining the form of multilateralism China is using to engage with Central Asia. The author believes that it is counterproductive to examine China’s use of multilateralism solely through the lens of western political science concepts. Given China’s 3,000 years of historical relations with foreign countries and the way China has been conducting its foreign policy with bordering countries as one single entity, one civilization, Chinese political culture has a very strong and unique history. Since China opened up to the West, many consider that it shares the same views as the West on international relations and political science. This perception is misleading and has led to confusion among many academics in their attempt to understand China. In order to avoid this confusion when explaining China’s approach to multilateralism, this research will use both contemporary and Chinese traditional concepts. The main research question of this paper is to what extent is China engaging in multilateralism in its relations with Central Asia? After analyzing China’s use of multilateralism in today’s international system, particularly with the Central Asian states, the analytical part of this research will address the extent to which China’s use of multilateralism matches classical multilateralism principles.